057 All Ireland Traveller Health Study: increasing gap in mortality between traveller and general populations in the Republic of Ireland over two decades. (16th November 2010) - Abdalla, S; Quirke, B; Daly, L; Fitzpatrick, P; Kelleher, C
Abstract : Background: Irish Travellers are a distinct minority group characterised by a nomadic lifestyle, specific culture and substantial socio-economic and health disadvantage. When examined in 1987 the Traveller community in the Republic of Ireland (ROI) were shown to have a higher mortality than the general population. Updated information was needed to inform policy action in this area. Objective: To examine the current mortality experience of Irish Travellers in the ROI and to contrast it with that of the general population. Design, setting and participants: We conducted a retrospective mortality count as part of a wider Traveller Census (The All Ireland Traveller Health Study). In ROI 9056 Traveller families were surveyed. Census respondents were asked to identify all immediate and extended family members who died over an exact 12 month period preceding the census date. Information obtained was corroborated with and supplemented by reports from the Traveller health networks, Public Health Nurses and General Registrar death records. Main outcome measures: Standardised mortality ratios (SMR) with 95% CI using the 2008 ROI general population mortality rates as standard. Results: There were 188 Traveller deaths in the year preceding the census date of October 14 th 2008. Traveller mortality in ROI is nearly three and a half times higher than that of the general population (SMR 348; 95% CI 298 to 397). This compares with a corresponding SMR of 254 calculated in 1987. Though general population mortality (age-adjusted) has declined by 35% over the past 20 years, Traveller mortality has only dropped by 13%, thus widening the mortality gap. Males have a significantly higher mortality than females with an SMR of 469 (95% CI 387 to 552) compared to a female SMR of 232 (95% CI 175 to 289). With a standard set of general population mortality rates in those aged 15 years and over, Travellers had an SMR of 277 (95% CI 235 to 319) compared to an SMR of 232 (95% CI 227 to 237) in the lower socio-economic group of the general population. Conclusion: Mortality among Irish Travellers has declined over the past 20 years but at a slower rate than that of the general population; the gap between Travellers and the general population has widened, particularly in males. The current gap is larger than that between the lower socio-economic group and the general ROI population. The results highlight the value of mortality measurement in uncovering health trends and health inequalities.